2021
DOI: 10.1523/jneurosci.2926-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin Interacts with the K-Cl Cotransporter KCC2 to Regulate Its Surface Expression and Function in Cortical Neurons

Abstract: The K 1 -Clcotransporter KCC2, encoded by the Slc12a5 gene, is a neuron-specific chloride extruder that tunes the strength and polarity of GABA A receptor-mediated transmission. In addition to its canonical ion transport function, KCC2 also regulates spinogenesis and excitatory synaptic function through interaction with a variety of molecular partners. KCC2 is enriched in the vicinity of both glutamatergic and GABAergic synapses, the activity of which in turn regulates its membrane stability and function. KCC2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 82 publications
1
20
0
Order By: Relevance
“…Premature overexpression of KCC2 disrupted brain development through a transport-independent interaction with the cytoskeleton-associated protein 4.1N ( Horn et al, 2010 ), while loss of KCC2 leads to excessive perinatal apoptosis ( Mavrovic et al, 2020 ), and KCC2 overexpression and pharmacological block lead to apoptosis in mature neurons ( Kontou et al, 2021 ). Studies of protein/protein interactions and work using transporter-deficient KCC2 mutants have revealed a previously unsuspected array of activity through interactions through membrane and cytoskeletal proteins ( Llano et al, 2020 ), such as kainate receptors ( Mahadevan et al, 2014 ), β-Pix ( Llano et al, 2015 ), KCNK9 channels ( Goutierre et al, 2019 ), gephyrin ( Al Awabdh et al, 2021 ), GABA B receptors ( Wright et al, 2017 ), and Neto2 ( Ivakine et al, 2013 ). Some of these interactions have effects independent of GABAergic signaling, such as increasing neuronal excitability through downregulating KCNK9 expression ( Goutierre et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature overexpression of KCC2 disrupted brain development through a transport-independent interaction with the cytoskeleton-associated protein 4.1N ( Horn et al, 2010 ), while loss of KCC2 leads to excessive perinatal apoptosis ( Mavrovic et al, 2020 ), and KCC2 overexpression and pharmacological block lead to apoptosis in mature neurons ( Kontou et al, 2021 ). Studies of protein/protein interactions and work using transporter-deficient KCC2 mutants have revealed a previously unsuspected array of activity through interactions through membrane and cytoskeletal proteins ( Llano et al, 2020 ), such as kainate receptors ( Mahadevan et al, 2014 ), β-Pix ( Llano et al, 2015 ), KCNK9 channels ( Goutierre et al, 2019 ), gephyrin ( Al Awabdh et al, 2021 ), GABA B receptors ( Wright et al, 2017 ), and Neto2 ( Ivakine et al, 2013 ). Some of these interactions have effects independent of GABAergic signaling, such as increasing neuronal excitability through downregulating KCNK9 expression ( Goutierre et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, KCC2 may still be involved in formation and plasticity of glutamatergic synapses in INs, which a follow-up study might investigate. On the other hand, GABA has been shown to promote neurite arborization and synaptogenesis of GABAergic synapses in multiple neuronal types ( Gascon et al, 2006 ; Ge et al, 2006 ; Bouzigues et al, 2007 ; Cancedda et al, 2007 ; Chattopadhyaya et al, 2007 ; Oh et al, 2016 ; Brady et al, 2018 ) and recently, an interaction between KCC2 and GABAergic synapse scaffolding protein gephyrin has been demonstrated ( Al Awabdh et al, 2021 ). Nonetheless, we found unremarkable expression of synaptic proteins and sIPSCs in layer 5 pyramidal neurons, suggesting normal development of GABAergic synapses in Dlx5 KCC2 cKO cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Gephyrin scaffolding interactions with non-receptor proteins provides an additional mechanism of synaptic regulation. For example, gephyrin directly interacts with and regulates the surface expression of the neuronal chloride extruder K + -Cl – cotransporter KCC2 ( Al Awabdh et al, 2022 ). KCC2 is expressed near both inhibitory and excitatory synapses ( Gulyás et al, 2001 ; Chamma et al, 2013 ) and is critical for generating the hyperpolarizing chloride gradient that allows for GABA A R inhibition in mature neurons.…”
Section: Interplay Between Glutamatergic and Gabaergic Synapsesmentioning
confidence: 99%
“…This may result from a low expression of KCC2 and a high expression of NKCC1 ( 85 ). Another study demonstrated that KCC2 expression was downregulated by glioma via increasing the intracellular Zn 2+ concentration in neurons, eliciting GABA-dependent depolarization of co-cultured neurons ( 86 ). These data implied that glioma may contribute towards epilepsy by influencing both glutamatergic and GABAergic signaling in neurons.…”
Section: Retroaction Of Glioma Cells On Neuronsmentioning
confidence: 99%